2000
DOI: 10.1007/s005340070012
|View full text |Cite
|
Sign up to set email alerts
|

Gallbladder volvulus: experience of six consecutive cases at an institute

Abstract: Recently we treated three patients with gallbladder volvulus within a short period. All three patients were examined preoperatively using computed tomography (CT). The first two cases were not diagnosed accurately before laparotomy. A precise diagnosis was made for the third one prior to surgery, based on our former experiences. Typical images, with marked edema and thickened wall of the gallbladder volvulus were shown on CT. We discuss six consecutive cases of the disease experienced at Hamamatsu Medical Cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 5 publications
0
19
0
Order By: Relevance
“…Elderly patients and patients with liver atrophy, decreased fat tissue in the abdomen, kyphoscoliosis, atherosclerosis of the cystic artery, and increased peristalsis of neighboring organs were defined as predisposal factors (7)(8)(9). GB stones were found in only 20%-50% of these patients, and it has been suggested that they had no importance as an etiological factor (10).…”
Section: Discussionmentioning
confidence: 99%
“…Elderly patients and patients with liver atrophy, decreased fat tissue in the abdomen, kyphoscoliosis, atherosclerosis of the cystic artery, and increased peristalsis of neighboring organs were defined as predisposal factors (7)(8)(9). GB stones were found in only 20%-50% of these patients, and it has been suggested that they had no importance as an etiological factor (10).…”
Section: Discussionmentioning
confidence: 99%
“…Eighty-five percent of these conditions occur between the ages of 60 and 80 years, with a female-to-male ratio of 3:1. 4 The history and physical findings are generally indistinguishable from those of acute cholecystitis, because most patients have nonspecific right-sided abdominal pain.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of anatomic and physiologic factors can contribute to such torsion. [1][2][3][4] The first such factor is a congenital anomaly in which abnormal migration with an absence of GB mesentery creates a free-floating GB. Another related group of factors includes generalized visceroptosis, atrophy of the liver, and loss of visceral fat and elasticity with aging and weight loss.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was first described in 1898 by Wendel (1) and approximately 500 or more cases have currently been reported in the literature. (2)(3)(4) Even with the recent advances in the radiologic imaging modalities, gallbladder torsion is a rare disease. The symptoms of this disease are largely non-specific, so making the preoperative diagnosis of gallbladder torsion is difficult, and the definite diagnosis is usually made at the time of surgery.…”
Section: Introductionmentioning
confidence: 99%